2006
DOI: 10.1590/s1135-57272006000600007
|View full text |Cite
|
Sign up to set email alerts
|

Desarrollo de un modelo de ajuste por el riesgo para el infarto agudo de miocardio en España: comparación con el modelo de charlson y el modelo ICES. Aplicaciones para medir resultados asistenciales

Abstract: The model developed may be a useful tool for assessing the hospital care provided for myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…35 Studies carried out by the Spanish Agencia de Evaluación de Tecnologías Sanitarias (Agency for the Evaluation of Heath Care Technologies) found a higher in-hospital mortality rate in AMI patients who did not undergo an interventional coronary procedure, 45 but they did not report differences in mortality related to the technological level of the centers. 16 The GYSCA study found that the treatment received by patients with non-ST elevation acute coronary syndrome admitted to hospitals with no catheterization laboratory differed more widely from that recommended by the guidelines; these investigators observed no significant differences in in-hospital mortality, but the incidence of readmission was significantly higher. 38 The MASCARA study found no relationship between the performance of primary percutaneous coronary intervention in patients with ST-elevation acute coronary syndrome and survival at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…35 Studies carried out by the Spanish Agencia de Evaluación de Tecnologías Sanitarias (Agency for the Evaluation of Heath Care Technologies) found a higher in-hospital mortality rate in AMI patients who did not undergo an interventional coronary procedure, 45 but they did not report differences in mortality related to the technological level of the centers. 16 The GYSCA study found that the treatment received by patients with non-ST elevation acute coronary syndrome admitted to hospitals with no catheterization laboratory differed more widely from that recommended by the guidelines; these investigators observed no significant differences in in-hospital mortality, but the incidence of readmission was significantly higher. 38 The MASCARA study found no relationship between the performance of primary percutaneous coronary intervention in patients with ST-elevation acute coronary syndrome and survival at 6 months.…”
Section: Discussionmentioning
confidence: 99%